The fountains of silence : a novel - Sepetys, Ruta (Philomel Books, 2019)
At the Castellana Hilton in 1957 Madrid, eighteen-year-old Daniel Matheson connects with Ana Moreno through photography and fate as Daniel discovers the incredibly dark side of the city under Generalissimo Franco's rule.